2006
DOI: 10.1007/s10708-006-9007-2
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the extent and causes of food insecurity in northern Ghana using a livelihood vulnerability framework

Abstract: The article describes the food insecurity situation in three villages in northern Ghana. A livelihood approach is used emphasising the vulnerability of the peasants' adaptation to a marginal and remote area. The peasant households are grouped according to level of food insecurity. It is argued that multiple income sources including non-farm activities are necessary to reduce food insecurity for all but a small part of the peasant households.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 16 publications
4
84
0
1
Order By: Relevance
“…• the effects of power and gender relations on the lives of specific groups of people (e.g., women) (Canagarajah et al 2001;Mandel 2004;Oberhauser and Pratt 2004), • the diversity of the strategies used by the rural poor to make a living (Abdulai and CroleRees 2001;Batterbury 2001;Smith et al 2001;Manvell 2006;Yaro 2006), • the success of climate change adaptation strategies Jones et al 2010;Osbahr et al 2010), • the effects of policies on the lives of the poor (Rakodi 1999;Barrett et al 2001), • issues of food security (Sutherland et al 1999;Gladwin et al 2001;Hesselberg and Yaro 2006;Codjoe and Owusu 2011), and • the effects of global environmental change on the poor (Hahn et al 2009). …”
Section: Sustainable Livelihoodsmentioning
confidence: 99%
See 4 more Smart Citations
“…• the effects of power and gender relations on the lives of specific groups of people (e.g., women) (Canagarajah et al 2001;Mandel 2004;Oberhauser and Pratt 2004), • the diversity of the strategies used by the rural poor to make a living (Abdulai and CroleRees 2001;Batterbury 2001;Smith et al 2001;Manvell 2006;Yaro 2006), • the success of climate change adaptation strategies Jones et al 2010;Osbahr et al 2010), • the effects of policies on the lives of the poor (Rakodi 1999;Barrett et al 2001), • issues of food security (Sutherland et al 1999;Gladwin et al 2001;Hesselberg and Yaro 2006;Codjoe and Owusu 2011), and • the effects of global environmental change on the poor (Hahn et al 2009). …”
Section: Sustainable Livelihoodsmentioning
confidence: 99%
“…They found that agriculture-based households could not rely on a single livelihood strategy, and cultural norms constrain women in their choice of livelihood strategies. Hesselberg and Yaro (2006) demonstrate that Ghanaian households require diverse livelihood strategies in order to reduce their food insecurity. They found that low food security is a result of poor biophysical conditions, low social capital and few opportunities for local non-farm income generating activities.…”
Section: Sustainable Livelihoodsmentioning
confidence: 99%
See 3 more Smart Citations